To Bet or Not to Bet : Copper Price Uncertainty and Investment in Chile - Comelli, Fabio; Perez Ruiz, Esther (Washington, D.C. : International Monetary Fund, 2016)
A strand of research documents Chile's copper dependence hence significant exposure to terms of trade shocks. Copper prices' sharp decline and forecast uncertainty since the end of the commodity super-cycle has rekindled the debate on Chile's adjustment capacity to external shocks. Following Malz (2014), this paper builds a time-varying measure of copper price uncertainty using options contracts. VAR analysis shows that the investment response to an uncertainty shock of average magnitude in the sample is strong and persistent: the cumulative fall in investment from trend at a one-year horizon ranges 2-5.8 percentage points; and it takes between 1 1\2 and 2 years for investment to return to its trend level. Empirical ranges depend on alternative definitions for investment, uncertainty, and options' maturing time.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet